Identification of novel cancer therapeutic targets using a designed and pooled shRNA library screen - Oliver, David; Ji, Hao; Liu, Piaomu; Gasparian, Alexander; Gardiner, Ellen; Lee, Samuel; Zenteno, Adrian; Perinskaya, Lillian O.; Chen, Mengqian; Buckhaults, Phillip; Broude, Eugenia; Wyatt, Michael D.; et al. (Scientific reports, 2017)
Targeted cancer therapeutics aim to exploit tumor-specific, genetic vulnerabilities specifically affecting neoplastic cells without similarly affecting normal cells. Here we performed sequencing-based screening of an shRNA library on a panel of cancer cells of different origins as well as normal cells. The shRNA library was designed to target a subset of genes previously identified using a whole genome screening approach. This focused shRNA library was infected into cells followed by analysis of enrichment and depletion of the shRNAs over the course of cell proliferation. We developed a bootstrap likelihood ratio test for the interpretation of the effects of multiple shRNAs over multiple cell line passages. Our analysis identified 44 genes whose depletion preferentially inhibited the growth of cancer cells. Among these genes ribosomal protein RPL35A, putative RNA helicase DDX24, and coatomer complex I (COPI) subunit ARCN1 most significantly inhibited growth of multiple cancer cell lines without affecting normal cell growth and survival. Further investigation revealed that the growth inhibition caused by DDX24 depletion is independent of p53 status underlining its value as a drug target. Overall, our study establishes a new approach for the analysis of proliferation-based shRNA selection strategies and identifies new targets for the development of cancer therapeutics.